Correction: Highly efficient construction of hollow Co–Nx nanocube cage dispersion implanted with porous carbonized nanofibers for Li–O2 batteries. Issue 7 (28th January 2022) - Peng, Lichong; Sun, Yaxin; Guo, Shiquan; Li, Congju
Abstract : Correction for 'Highly efficient construction of hollow Co–N x nanocube cage dispersion implanted with porous carbonized nanofibers for Li–O2 batteries' by Lichong Peng et al., J. Mater. Chem. A, 2022, 10, 740–751, DOI: ; 10.1039/D1TA09008A .